Security Measures and Criminal Justice Reform: A Perspective from Human Rights - Plascencia Villanueva, Raul (2010)
The present paper analyzes, from the perspective of human rights, the development of insurance measures in Mexico. The author affirms that the measures of assurance, also called precautionary measures or coercive measures, have as main objective to ensure criminal execution. These have a direct impact on human rights, because they restrict, in a general sense, freedom. Rights such as the area of ??personal freedom, the right relative to bodily integrity, the right to informative self-determination, among others, are violated; likewise, insurance measures can affect people's assets. In this sense, the doctrine establishes two types of insurance measures: personal coercion and real coercion. Regarding the first, these are those related to the subjects, that is, to the people. The author establishes some of the personal precautionary measures: i) affectation to bodily integrity, ii) disqualification from exercising activity, trade or profession, iii) interference in private life and intervention in communications, iv) rooted, v) detention and vi) apprehension. On the other hand, the real assurance measures are those that refer to the property, be it movable or immovable. It is necessary to point out that the CPEUM (Political Constitution of the United Mexican States) establishes the inviolability of the domicile; however, this principle is relative, in certain cases established by law this is allowed, for example, in cases of serious crimes or flagrancy. Finally, the author analyzes the rooted precautionary measure. The Supreme Court of Justice of the Mexican Nation establishes the unconstitutionality of house arrest; nevertheless, this is practiced. It is also noted that this figure is not currently used as a precautionary measure, but as a criminal legal consequence; in other words, as a penalty that has not been decreed or imposed by a judge. This directly affects the freedom of people and is comparable to penalties such as pretrial detention.